Pengaruh Citra Merek, Kepercayaan Merek, dan Duta Merek terhadap Keputusan Pembelian: Studi Industri Smartphone di Pulau Lombok - Muhammad Arsyad; St Hatidja (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study examines the influence of Brand Image, Brand Trust, and Brand Ambassadors on Purchase Decisions in the context of the mid-range smartphone industry on Lombok Island. Involving 120 respondents, this study analyzes the extent to which these three variables play a role in shaping consumer behavior and preferences. The results show that Brand Image has a dominant influence in determining consumer choices. Consumers tend to be more attracted to smartphone brands with a positive image, which then has implications for their purchase decisions. Furthermore, Brand Trust has been proven to be an important foundation in building long-term relationships between consumers and brands. A high level of trust encourages consumers to choose products from brands that are considered credible and reliable. Brand Ambassadors also play a significant role in improving purchase decisions, as seen by the positive correlation between Brand Ambassador effectiveness and increased consumer interest in the product. The practical implications of this study highlight the importance for smartphone companies to focus on strengthening brand image through consistent communication strategies and positive customer experiences. Efforts to build brand trust must be carried out by maintaining product quality, fulfilling brand promises, and creating transparency in after-sales service. Furthermore, selecting a Brand Ambassador whose values ​​and characteristics align with the target market segment can increase consumer appeal and loyalty to the brand. This study contributes to the consumer behavior literature by offering a comprehensive analysis of the relationship between Brand Image, Brand Trust, Brand Ambassadorship, and Purchase Decisions. These findings enhance understanding of the factors influencing consumer purchasing decisions in the mid-range smartphone market on Lombok Island and provide strategic recommendations for industry players to enhance their brand competitiveness and success.